2020
DOI: 10.29121/granthaalayah.v7.i10.2019.381
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of the Use of Instagram Among Adolescent Girls

Abstract: Social media provides opportunities for users to express their thoughts and feelings through writing, pictures and videos. The rich features of this platform make Instagram the most preferred platform for adolescents, including teenagers in Indonesia. Various activities can be done through Instagram such as building friendships, seeking information and entertainment. The phenomenon of communicating online especially on Instagram can be observed through self-penetration theory that observes the closeness of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The findings indicate that teenagers are in a developmental stage where they highly prioritise the approval and recognition of others. This aligns with a study conducted by Maryani et al (2020), which revealed that female teenage participants relied on Instagram as a means of expressing their emotions and establishing a sense of identity within their social circle. Teenage girls, in particular, use Instagram to share photographs and material to gain favorable comments from their peers, which serves as a source of motivation for them to become more famous and enhance their attractiveness (Meeus et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The findings indicate that teenagers are in a developmental stage where they highly prioritise the approval and recognition of others. This aligns with a study conducted by Maryani et al (2020), which revealed that female teenage participants relied on Instagram as a means of expressing their emotions and establishing a sense of identity within their social circle. Teenage girls, in particular, use Instagram to share photographs and material to gain favorable comments from their peers, which serves as a source of motivation for them to become more famous and enhance their attractiveness (Meeus et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…As of September 2017, Instagram has been used by 800 million users with almost 60% of them aged 18-29. The study also cited Chase's statement (in Maryani et al, 2020) about Instagram's diverse functions , "Social media has a variety of functions that attract users, where users can have conversations, build identities, group and maintain their reputation." Instagram is also widely chosen because as a social media Instagram is able to integrate various media content platforms such as text, images, and even videos, efficiently in terms of time because information can be quickly spread and shared by its users synchronously, even users can converse directly through chat features or live IG, users do not need hard efforts or special skills to be able to use it, social media users can edit and revise information, the wrong and useless information in social media will be filter out.…”
Section: Discussionmentioning
confidence: 92%
“…Based on the research findings that have been described in the results section, Instagram is currently the most widely used media by PIK-R managers to convey information, especially during the pandemic. Based on research on the use of Instagram by young women in Bandung (Maryani et al, 2020), Instagram is widely used by teenagers because of the completeness of its features so that it is seen as more comfortable to use than other social media. As of September 2017, Instagram has been used by 800 million users with almost 60% of them aged 18-29.…”
Section: Discussionmentioning
confidence: 99%
“…The visual and textual elements (i.e., images, videos, titles, comments) of an Instagram post are full of current and time-bound cultural information. By analyzing these images and comparing them with images from other cultures of their own, students can develop critical thinking and broaden their global perspectives (Amâncio & Doudaki, 2017;Bell, 2013;Maryani et al, 2020).…”
Section: Instagram Featuresmentioning
confidence: 99%